Translating caste - Kalitā, Arūpā Paṭaṃgīẏā.; Basu, Tapan (New Delhi : Katha, 2002)
Volume comprises eight translated short stories on the theme of caste along with contributed articles on socio-cultural aspects of caste in modern India.
"A Katha classroom text"--Cover.
Bibliography p.xxxiii-xxxv
Includes bibliographical references (p. [243]-248) and index.
Keywords: Short stories, Indic -- Translations into English; Indic fiction -- 20th century -- Translations into English; Caste in literature; Caste -- India; India -- Social conditions -- 1947-